The Middle Period, 1817-1858 - Burgess, John William, 1844-1931 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Middle Period, 1817-1858" by John W. Burgess is a historical account written in the early 20th century. The book analyzes a pivotal era in American history characterized by significant political, social, and territorial changes leading up to the Civil War. The author aims to provide a comprehensive yet impartial examination of this timeframe, focusing on events, legislation, and the evolving philosophies that shaped the nation during this transformative period. The opening of the work establishes the author's approach to writing about the complex and often contentious issues of American history between 1816 and 1860. Burgess acknowledges the challenges of exploring this era due to the passions involved, particularly concerning the North-South divide. He emphasizes his commitment to impartiality while outlining his intention to clarify misunderstandings that linger today between different sections of the country. Burgess sets the stage for a detailed exploration of political developments, such as the evolution of the Republican Party and key legislative measures, along with their impact on both regional and national dynamics. (This is an automatically generated summary.)
Release date is 2011-03-12
Produced by Ron Swanson
Keywords: United States -- Politics and government -- 1815-1861; United States -- History -- 1815-1861